2003
DOI: 10.1590/s0006-87052003000200009
|View full text |Cite
|
Sign up to set email alerts
|

Influência de tricomas do algodoeiro sobre os aspectos biológicos e capacidade predatória de Chrysoperla externa (Hagen) alimentada com Aphis gossypii Glover

Abstract: RESUMOOs tricomas do algodoeiro atuam como um dos fatores de resistência a Aphis gossypii Glover, e podem afetar também seus inimigos naturais, reduzindo a eficiência desses agentes de controle e aumentando o tempo de procura pela presa. Neste trabalho, em condições de laboratório, avaliou-se a influência da densidade de tricomas das cultivares de algodoeiro Antares (pouco pilosa), CNPA 7H (hirsuta) e Deltapine Acala 90 (pilosa) sobre os aspectos biológicos e a capacidade predatória de Chrysoperla externa (Hag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
(11 reference statements)
0
8
1
4
Order By: Relevance
“…The A. gossypii population attack preferentially in young leaves, which are generally located on the apical parts (CHAU et al, 2005;SANTOS et al, 2003). However, in the present study, we observed higher attack of this insect in the bottom and medium rather than in the apical part of okra plants.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…The A. gossypii population attack preferentially in young leaves, which are generally located on the apical parts (CHAU et al, 2005;SANTOS et al, 2003). However, in the present study, we observed higher attack of this insect in the bottom and medium rather than in the apical part of okra plants.…”
Section: Discussioncontrasting
confidence: 76%
“…(CHAU et al, 2005;MEN et al, 2004;RHAINDS & MESSING, 2005;SANTOS et al, 2003;SOGLIA et al, 2002SOGLIA et al, , 2003, leaf N and K, leaf organic compounds analyzed and trichomes were apparently not important in this study. The trichomes (% non-glandular) found in okra were of low density and did not contain toxic compounds, which could present antibiotic and nonpreference effects.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations